Factors Influencing ICT Utilization in Select Institutions of Higher Education in India - Kapoor , Minakshi; Mehta, Versha (Gyan Management Journal, 2016)
The organizations worldwide, due to ever increasing constraints on time and space are increasingly recognising the need to facilitate access to services through the exchange of information using information and communication technologies. It has been seen based upon the literature review that ICTs are used by people and organizations for their information processing and communication purposes in a relatively simple and basic manner, however, its utilization has not been so valuable. In this context and background, the present study investigates a set of factors and their influence on /CT utilization in select organizations in the higher education sector. A sample of 150 respondents from the University of jammu and Panjab University have been surveyed to identify the factors affecting the users’ intention to use ICTs. The factor analysis has resulted in a total of 11 factors having 45 items in all. The data thus collected has been analyzed using different statistical techniques which includes descriptive statistics i.e. mean and standard deviation. The paper has established the relationships between variables viz. attitude, belief, self-efficacy, accessibility, ease of use and so on for the utilization of information technologies.